Silica-on-silicon waveguide circuits and superconducting detectors for integrated quantum information processing - Metcalf, B (2014)
Building complex quantum systems has the potential to reveal phenomena that cannot be studied using classical simulation. Photonics has proven to be an effective test-bed for the investigation of such quantum-enhanced technologies, however, the proliferation of bulk optical components is unlikely to be a scalable route towards building more complex devices. Instead, the miniaturisation, inherent phase stability and trivial alignment afforded by integrated photonic systems has been shown to be a promising alternative. In the first half of this thesis, we describe experiments exploiting the quantum interference of three single photons on a reconfigurable integrated photonic chip. We develop a low-loss source of single photons and introduce a low-loss silica-on-silicon waveguide architecture which enables us to show the first genuine quantum interference of three single photons on an integrated platform. A loss-tolerant, element-wise characterisation scheme is developed along with a statistical test to verify that this multi-photon circuit behaves as expected. We then make use of this three-photon interference to detail the first proof-of-principle demonstration of a new intermediate model of quantum computation called boson sampling. Finally, we perform an on-chip demonstration of the quantum teleportation protocol where all key parts --- entanglement preparation, Bell-state analysis and quantum state tomography --- are performed on a reconfigurable photonic chip. The element-wise characterisation scheme developed earlier is shown to be critical to mitigate fabricated component errors. We develop a theoretical model to account for all sources of possible error in the circuit and find good agreement with the measured teleported state fidelities, which exceed the average teleportation fidelity possible with a classical device. We identify the elements of this error budget relevant to scaling and propose improvements to chip characterisation and fabrication in order to achieve high fidelity operation. In the second half, we discuss the use of high efficiency superconducting transition edge sensors in enabling quantum experiments using more photons. We detail the installation and characterisation of these detectors in a new lab in Oxford. We achieve good photon number-resolution and high-efficiency operation. Work to integrate these detectors on the silica-on-silicon waveguide architecture is discussed and we detail the optical and thermal device modelling performed to optimise the on-chip detection efficiency. New, on-chip detectors, fabricated according to this design are shown to operate as expected and achieve high-efficiency and good energy resolution.